Simple and sensitive determination of sparfloxacin in pharmaceuticals and biological samples by immunoassay - Hua-Jin Zeng; Ran Yang; Bing Liu; Li-Fang Lei; Jian-Jun Li; Ling-Bo Qu (Elsevier, 2012)
Plasma quinolone concentrations are not routinely measured in clinical practice. However, in order to optimize quinolone treatment, monitoring of plasma concentrations could sometimes be useful particularly in critically ill patients. In this study, anti-sparfloxacin antibody was obtained by immunizing rabbits with sparfloxacin conjugated with bovine serum albumin using isobutyl chloroformate method. After the assay procedure was optimized, the standard curve of sparfloxacin was established. The practical measuring range of the competitive ELISA extended from 5Â ng/mL to 2Â Î¼g/mL. The recovery rates and coefficients of variation for rat plasma, urine and tissues were 87.7â106.2% and 4.8â15.3%, respectively. To demonstrate the potential of the ELISA, a preliminary pharmacokinetics and tissue distribution study of sparfloxacin in rats and quantitative analysis of sparfloxacin in several pharmaceuticals were performed and compared with high-performance liquid chromatography (HPLC). The experimental data indicated that the proposed method would be a valuable tool in therapeutic drug monitoring (TDM) for sparfloxacin. Keywords: Sparfloxacin, Enzyme-linked immunosorbent assay (ELISA), Biological samples, Pharmacokinetics, Tissue distribution